Youth Empowerment for Productive Economic Efforts in the Use of Coconut Charcoal Shells - Mochamad Mu’izzuddin; Hunainah Hunainah; Sulaiman Jazuli; Anis Fauzi (International Journal of Community Service & Engagement, 2023)
The use of coconut fruit waste (coco nucifera) is still very open to be studied and further developed in Indonesia as a tropical country that has very abundant natural resources to be utilized optimally. This is also considering that although almost all parts of the coconut fruit have been taken advantage of, many are also wasted into waste such as the fibers and shells. One of the uses of coconut shells is used as charcoal fuel. Coconut shell charcoal is usually further processed into briquettes and until now is used by the community for household, business, and industrial purposes. The use of coconut shells can be done to overcome wastewater.Changes and village building initiatives must grow from young people or millennials who act as agents of change. The research approach used is a type of pedagogic approach that leads to providing a description of the object of research and its relation to everything studied in the form of interviews and the results of the author’s observations during the activity and after the activity. In this study, a qualitative descriptive design type was used. Researchers are trying to obtain and describe data about this service activity in the form of Training on Making Shells into Charcoal with the theme “Training on Making charcoal into shells in Kedung Soka Village, Ampel Island District, Serang Regency, Banten Province, Indonesia”.